Transformational leadership style of Supervisors/Heads as Perceived by the Employees and the attitude of employees toward the School - Abun, Damianus; Gladys Jean Q. Basilio,; Theogenia Magallanes,; Maricel B. Quadra,; Mary Joy Encarnacion, (Technium Social Sciences Journal, 2020)
The study intended to determine the effect of the transformational leadership style of supervisors/heads toward the attitude of employees to the school. To carry out the study, the related literature was reviewed to strengthen the theory of the study. The population of the study was all employees of the two colleges in the two provinces. It used questionnaires to gather the data and used a descriptive correlational research design. The weighted mean was used to determine the transformational leadership and attitude level and the Pearson r or Product Moment of Correlation was used to determine the correlation between transformational leadership style and the attitude of employees toward the school. The study found that there is a significant correlation between the two variables and therefore the hypothesis of the study is accepted.